Personality and Background Characteristics in Patients with Methamphetamine-Induced Psychosis - Nazari, Ali; Hojjat, Seyed Kaveh; Khorrami, Mohammad; Kaviyani, Faezeh; Jafakesh Moghaddam, Asiyeh; Akbari, Hadi; Gholizadeh, Nazanin; Niloofar, Parastoo; Fazeli, Ali (International Journal of Education and Cognitive Sciences, 2026)
Purpose: This study aimed to examine the association between personality traits and the occurrence of psychosis among methamphetamine users.Methods and Materials: A descriptive, cross-sectional study was conducted among 200 adults with confirmed methamphetamine dependence recruited from addiction treatment centers in North Khorasan Province, Iran. Methamphetamine-induced psychosis was diagnosed using structured clinical interviews based on DSM-5 criteria, initially by a clinical psychologist and then confirmed by a psychiatrist. Personality characteristics were assessed with the Millon Clinical Multiaxial Inventory-III (MCMI-III), adapted and validated for the Iranian population. Demographic and background data—including age, gender, education, marital and employment status, housing, and concurrent substance use—were collected via structured questionnaires. Statistical analyses were performed using independent-samples t-test, Mann–Whitney U test, and chi-square test at a significance level of p < 0.05.Findings: Significant differences were observed between psychotic and non-psychotic methamphetamine users across several personality domains. Psychotic individuals scored higher on schizoid, schizotypal, paranoid, avoidant, dependent, depressive, sadistic, negativistic, masochistic, and borderline traits (p < 0.05), while histrionic traits were significantly lower in the psychotic group (p = 0.016). Demographically, psychotic users were more likely to have lower education (p = 0.043) and to be unmarried or divorced (p = 0.048). Polysubstance use was common, with concurrent use of methamphetamine with opium (55.5%) and heroin (55%) being most frequent.Conclusion: Specific personality patterns, particularly within Clusters A and B, are strongly associated with methamphetamine-induced psychosis. Incorporating personality assessment into addiction treatment may improve risk detection and enable personalized interventions to prevent or mitigate psychotic outcomes among methamphetamine users.